6. Tashmiimu As’ilati at-Taqyiimi Lita’liimi al-Lughati al-Arabiyati a’la Asasi adz-Dzakaati al-Mutaaddidati - Ibadurrahman Ali; Dewi Chamidah (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
This research aims to design evaluation questions for Arabic language learning based on multiple intelligences. The research methodology employed is qualitative descriptive with a literature study approach. Data collection is conducted through documentation by analyzing relevant literature, references, and sources related to Arabic language learning and multiple intelligences theory. The data analysis results indicate that for linguistic intelligence, independent tasks can be used as the form of evaluation questions. In the context of kinesthetic intelligence, project-based tasks such as Arabic language dramas can be utilized. For musical intelligence, students can be asked to create children's songs using Arabic vocabulary. Regarding intrapersonal intelligence, group work methods such as the jigsaw method can be employed as the form of evaluation questions. In conclusion, by considering multiple intelligences in evaluating Arabic language learning, teachers can provide equal opportunities for all students to showcase their intelligence in Arabic language acquisition.